Investigation of Leaching Characteristics of Coal Ash - Sharma, Nakul (My University, 2014)
The present study on the investigation of the mineralogical and physio-chemical properties of fly ash was conducted at the MED Department, Thapar University, and Patiala. Three Fly ash samples were taken from three different thermal power plants namely Ropar, Hisar and Bhatinda Thermal Power stations of varied specific gravity and densities. Leaching Tests on Coal ash was performedusing TCLP(Toxicity leaching procedure) approach at Mechanical Engineering Department and for studying Physical properties of Coal ash Tests such as XRD(X-ray diffraction),DTA(Differential Thermal analysis) ,SEM(Scanning Electron Microscopy) and EDS(Energy Dispersive Spectroscopy) were performed on three samples of Fly and Bottom ash. It was observed from XRD tests that these samples consists mainly of minerals such as Quartz, Mullite, Hematite and kynamite as their main constituents along with traces of other components. Volume fraction was calculated to determine the content of these minerals in Coal ash.XRD peaks showed that these Minerals were mostly in crystalline phase.EDS tests were performed on samples with and without Leachates. Samples without Leachate showed Silicon (Si), Aluminum (Al) and Iron (Fe) as main constituents along with traces Of Titanium (Ti), Potassium, Calcium (Ca) and Zirconium (Zr) and Samples with Leachates showed reduction in content of these elements due to leaching. Also SEM (Scanning Electron Microscopy) tests were performed on Coal ash leachates and Coal ash without leachates.It revealed the changes in morphology from uniform, spherical glassy spherical particles (in case of non –leachates) to less uniform, irregular and coarse particles with changes in shape and size(in case of leachates).Lastly AAS (Atomic absorption spectroscopy) was performed on Bhatinda fly ash leachate. Results revealed concentration(mg/l) of some elements such as Cd (Cadmium), Cr (Chromium), and Pb (Lead) well above the WHO limit on drinking water.
Master of Engineering-Thesis
Keywords: leaching; PHYSICAL AND CHEMICAL PROPERTIES; mechanical engineering